2007
DOI: 10.1194/jlr.m700021-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

The components required for amino acid neurotransmitter signaling are present in adipose tissues

Abstract: The adipocyte does not only serve as fuel storage but produces and secretes compounds with modulating effects on food intake and energy homeostasis. Although there is firm evidence for a centrally mediated regulation of adipocyte function via the autonomous nervous system, little is known about signaling between adipocytes. Amino acid neurotransmitters are candidates for such paracrine signaling. Here, we applied immunohistochemistry to detect components required for amino acid transmitter signaling in rat fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…GABA A -R subunits are expressed by immunocompetent cells, including T cells and macrophages and are also expressed by adipose tissues [13], [14], [15], [17]. Our previous studies and those of others have shown that treatment with GABA or a GABA A receptor agonist inhibits inflammation in different mouse models of autoimmune diseases [16], [17], [18], [20], [21].…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…GABA A -R subunits are expressed by immunocompetent cells, including T cells and macrophages and are also expressed by adipose tissues [13], [14], [15], [17]. Our previous studies and those of others have shown that treatment with GABA or a GABA A receptor agonist inhibits inflammation in different mouse models of autoimmune diseases [16], [17], [18], [20], [21].…”
Section: Resultsmentioning
confidence: 88%
“…Given that GABA A -R subunits are expressed by macrophages and adipose tissues [13], [15], we further tested whether GABA could modulate macrophage-associated inflammation in adipose tissues, or alter adipose tissue mass in the HFD-fed mice. Following HFD feeding for 20 weeks, control and GABA-treated mice were sacrificed and their VAT was dissected out and weighed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…97 Other amino acid neurotransmitters are also found in the adipose tissue; with immunohistochemical labeling used to detect gamma amino butyric acid (GABA), glutamate, the GABA producing enzyme glutamate decarboxylase, and transporters and receptors for glutamate and GABA. 98 There is also regulation by POMC peptides in adipose tissue to promote browning of WAT and lipolysis, 99,100 and sympathetic innervation of the adipose tissue. 101 The neurotransmitter NPY has received much attention in recent years, highlighted in our recent review, 18 but is still an active area of research, which is reviewed herein.…”
mentioning
confidence: 99%